2020
DOI: 10.3389/fimmu.2020.566732
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Flow Cytometric Detection of Residual B-Cells After Rituximab in Anti-Neutrophil Cytoplasmic Antibodies-Associated Vasculitis Patients

Abstract: BackgroundB-cell depletion with rituximab (RTX) is an effective treatment for anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) patients. Nevertheless, relapses are frequent after RTX, often preceded by B-cell repopulation suggesting that residual autoreactive B-cells persist despite therapy. Therefore, this study aimed to identify minimal residual autoimmunity (MRA) in the B-cell compartment of AAV patients treated with RTX.MethodsEuroFlow-based highly-sensitive flow cytometry (HSFC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…First, CD19 CAR T cells were highly efficient and depleted B cells (nearly) completely. In contrast, high-sensitive flow cytometry shows residual B cells, including ANCA-specific memory B cells at all time-points after rituximab administration in AAV patients 31. Second, we found that CD19 CAR T cells engrafted in lymphoid organs and inflamed target organs, such as kidneys.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…First, CD19 CAR T cells were highly efficient and depleted B cells (nearly) completely. In contrast, high-sensitive flow cytometry shows residual B cells, including ANCA-specific memory B cells at all time-points after rituximab administration in AAV patients 31. Second, we found that CD19 CAR T cells engrafted in lymphoid organs and inflamed target organs, such as kidneys.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, high-sensitive flow cytometry shows residual B cells, including ANCA-specific memory B cells at all time-points after rituximab administration in AAV patients. 31 Second, we found that CD19 CAR T cells engrafted in lymphoid organs and inflamed target organs, such as kidneys. This finding provides an advantage over B cell-targeting antibodies that result in incomplete tissue B cell depletion.…”
Section: Discussionmentioning
confidence: 78%
“…Allerdings profitieren nicht alle Patienten gleichermaßen, wie nicht zuletzt die hinter den Erwartungen zurückbleibenden Phase-II/III-Studien zu Rituximab und SLE demonstrierten [18,19]. Als Gründe werden die Persistenz autoreaktiver B-Zellen sowohl im peripheren Blut als auch in Organstrukturen diskutiert [20][21][22]. Abzuwarten bleibt, ob die neuere Generation an anti-CD20-Antikörpern dies ändern wird.…”
Section: Wirkweise Der Car-t-zell-therapieunclassified
“…As a result of this, the last recommendations do not support the use of tailored-administration strategy as a first-line maintenance treatment, suggesting that more data on this field are needed. On this respect, van Dam et al employed highly-sensitive flow cytometry (HSFC), traditionally used to detect minimal residual disease in haematologic neoplasia, to perform a phenotypic analysis of the B-cell compartment in patients undergoing RTX treatment for either induction or remission maintenance (92). They showed that RTX induced strong reductions in circulating Bcells, but never resulted in complete Bcell depletion when the serum samples were analysed by HSFC, in contrast to conventional low-sensitive flow cytometry.…”
Section: S-9mentioning
confidence: 99%